2022
DOI: 10.1002/iid3.645
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of 3′UTR HLA‐G14‐bp insertion/deletion and +3142 C/G polymorphisms and soluble HLA‐G expression with gynecological cancers: An updated meta‐analysis

Abstract: Objectives Human leukocyte antigen‐G (HLA‐G) is implicated in several cancers and is considered to be an immune checkpoint regulator. We determined the association between polymorphisms in the 3′ untranslated region of HLA‐G and soluble HLA‐G (sHLA‐G) expression with gynecological cancers (GCs). Methods A meta‐analysis was conducted to examine the association between HLA‐G14‐bp insertion ( I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Other works and meta-analysis described an association of HLA-G 3'UTR haplotypes to the development and severity of different malignancies, such as breast and colorectal cancer, were 14bp Del/Del and + 3142 C/C, both forming UTR-1 and UTR6 haplotypes, showed association to risk of developing both cancers (20,21). Moreover, other authors showed an association of HLA-G levels of expression and the 14bp polymorphism in gynecologic cancers (22), and, in the same vein of thinking, loss of miR-152 increases HLA-G expression in vitro (23), mimicking the effect of + 3142 polymorphisms, as miR-152 is not able to bind + 3142 C/C. All these ndings not only support the results of our work, but also provide a functional explanation for them, as it seems clear that there is a link between variants in the 3'UTR of HLA-G and the expression levels of this protein and, consequently, with the risk of developing tumors of epithelial origin.…”
Section: Discussionmentioning
confidence: 93%
“…Other works and meta-analysis described an association of HLA-G 3'UTR haplotypes to the development and severity of different malignancies, such as breast and colorectal cancer, were 14bp Del/Del and + 3142 C/C, both forming UTR-1 and UTR6 haplotypes, showed association to risk of developing both cancers (20,21). Moreover, other authors showed an association of HLA-G levels of expression and the 14bp polymorphism in gynecologic cancers (22), and, in the same vein of thinking, loss of miR-152 increases HLA-G expression in vitro (23), mimicking the effect of + 3142 polymorphisms, as miR-152 is not able to bind + 3142 C/C. All these ndings not only support the results of our work, but also provide a functional explanation for them, as it seems clear that there is a link between variants in the 3'UTR of HLA-G and the expression levels of this protein and, consequently, with the risk of developing tumors of epithelial origin.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, several studies have debated the regulation of sHLA-G levels by HLA-G 3’UTR polymorphisms. These disputes may vary among different populations with different genetic backgrounds ( 17 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta‐analysis confirmed that HLA‐G+3142 C/G is significantly associated with reduced susceptibility to cervical cancer. Similarly, HLA‐G14‐bp I/D was found to be significantly associated with HPV‐induced cervical prelesions (Tizaoui et al., 2022).…”
Section: Hla‐g In Cervical Cancermentioning
confidence: 96%
“…A recently published meta-analysis confirmed that HLA-G+3142 C/G is significantly associated with reduced susceptibility to cervical cancer. Similarly, HLA-G14-bp I/D was found to be significantly associated with HPV-induced cervical prelesions(Tizaoui et al, 2022).Third, the upregulation of HLA-G expression favours the persistence of HPV in a microenvironment of a submissive host response Xu et al (2018). showed that significantly increased prevalence of HLA-G* 3′ UTR 14-bp ins among 495 Chinese Han women infected with HPV18 (38.5% vs. 29.2%, p < .05; OR, 1.52) was associated with the progression of HPV18-related cervical lesions.…”
mentioning
confidence: 89%